METODE PENGEMBANGAN PERANGKAT LUNAK BERBASIS MOBILE: A REVIEW - Firamon Syakti (Jurnal Ilmiah Terpadu Universitas Bina Darma, 2019)
Internet users in Indonesia always increase every year. The highest increase occurred in smartphone internet users. The increase was due to a shift in the provision of software from desktop and web to mobile based. Based on these conditions it is necessary to know the process of providing mobile applications to suit users. Provision of mobile applications cannot be separated from the process of software development, especially the development of mobile software. For this reason, in this study a discussion on mobile software development methods consisting of wireless development, mobile application development lifecycle models (MADLC) and mobile development (Mobile-D) was discussed. the three methods of developing mobile wireless development software have the longest working phase, which is eight phases, while the mobile application development lifecycle model (MADLC) has seven phases and mobile development (Mobile-D) has five phases. The choice of mobile software development methods is an important factor in the development process. Pengguna internet di Indonesia setiap tahunya selalu meningkat. Peningkatan yang paling tinggi terjadi pada pengguna internet smartphone. Peningkatan tersebut disebabkan adanya pergeseran penyediaan perangkat lunak dari desktop dan web ke berbasis mobile. Berdasarkan kondisi tersebut perlu untuk diketahui proses penyediaan aplikasi mobile agar sesuai dengan pengguna. Penyediaan aplikasi mobile tidak terlepas dari proses pegnembangan perangkat lunak terutama pengembangan perangkat lunak mobile. Untuk itu didalam kajian ini dilakukan pembahasan metode pengambangan perangkat lunak mobile yang terdiri dari wireless development, mobile application development lifecycle model (MADLC) dan mobile development (Mobile-D). Dari ketiga metode pengembangan perangkat lunak berbasis mobile wireless development memili fase pengerjaan paling Panjang yaitu delapan fase, sedangkan mobile application development lifecycle model (MADLC) memiliki tujuh fase dan mobile development (Mobile-D) memiliki lima fase. Pemilihan metode pengembangan perangkat lunak mobile menjadi faktor penting dalam proses pengembangan.